Dislocating Masculinity: Comparative Ethnographies - Nardini, Krizia (Quaderns de l’Institut Català d’Antropologia, 2019)
Andrea Cornwall, Lindisfarne Nancy, Ed. (1994) Dislocating Masculinity: Comparative Ethnographies London: Routledge, 236 p. ISBN: 0-415-07941-1.